An ATF/CRE Element Mediates both EBNA2-Dependent and EBNA2-Independent Activation of the Epstein-Barr Virus LMP1 Gene Promoter - Sjöblom, Anna (American Society for Microbiology, 1998)
The Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) is a viral oncogene whose expression is regulated by both viral and cellular factors. EBV nuclear antigen 2 (EBNA2) is a potent transactivator of LMP1 expression in human B cells, and several EBNA2 response elements have been identified in the promoter regulatory sequence (LRS). We have previously shown that an activating transcription factor/cyclic AMP response element (ATF/CRE) site in LRS is involved in EBNA2 responsiveness. We now establish the importance of the ATF/CRE element by mutational analysis and show that both EBNA2-dependent activation and EBNA2-independent activation of the promoter occur via this site but are mediated by separate sets of factors. An electrophoretic mobility shift assay (EMSA) with specific antibodies showed that the ATF-1, CREB-1, ATF-2 and c-Jun factors bind to the site as ATF-1/CREB-1 and ATF-2/c-Jun heterodimers whereas the Sp1 and Sp3 factors bind to an adjacent Sp site. Overexpression of ATF-1 and CREB-1 in the cells by expression vectors demonstrated that homodimeric as well as heterodimeric forms of the factors transactivate the LMP1 promoter in an EBNA2-independent manner. The homodimers of ATF-2 and c-Jun did not significantly stimulate promoter activity. In contrast, the ATF-2/c-Jun heterodimer had only a minor stimulatory effect in the absence of EBNA2 but induced a strong transactivation of the LMP1 promoter when coexpressed with this protein. Evidence for a direct interaction between the ATF-2/c-Jun heterodimeric complex and EBNA2 was obtained by EMSA and coimmunoprecipitation experiments. Thus, our results suggest that EBNA2-induced transactivation via the ATF/CRE site occurs through a direct contact between EBNA2 and an ATF-2/c-Jun heterodimer. EBNA2-independent promoter activation via this site, on the other hand, is mediated by a heterodimeric complex between the ATF-1 and CREB-1 factors.